Effects of the Combined Alum and Melatonin on Immune Responses in NMRI Mice Immunized with the Killed Preparation of Salmonella Typhimurium - Zahra Jvadi; Seyyed Meysam Abtahi Froushani; Melahat Ahmadi (Fasa University of Medical Sciences, 2020)
Background & Objectives: Melatonin is one of the immuno-modulator compounds. The purpose of this study was to determine the feasibility of improving immune responses following the use of melatonin in a vaccine made from the killed form of Salmonella typhimurium and alum. Materials & Methods: This experimental study consists of 50 male NMRI mice that were allocated in 5 equal groups, randomly. Each mouse in different groups was subcutaneously treated with killed preparations of bacteria (106 CFU), killed preparations of bacteria with alum, killed preparation bacteria with melatonin (100mg/kg), combined melatonin and alum with killed preparation bacteria, and finally PBS at two-week intervals. One week after the last immunization, one-half of the mice were euthanized and used for immunological evaluations. Other mice in each group were challenged intraperitoneally with the 107CFU live preparation of S.typhimurium in order to evaluate the protective efficacy of vaccine protocols. Results: Combined vaccine caused a more favorable survival curve concurrent with a significant increase in the delayed-type hypersensitivity immune response and lymphocyte proliferation after challenging with bacterial antigen compared to other groups (P<0.05). The antibody titers against O and H antigens in the Widal test showed an increase in the alum group more than the melatonin group. The antibody titers showed an increase in the combined group. Nevertheless, this change did not show any significant effect in comparison with the alum group. Conclusion: Combined melatonin and alum caused a significant increase in immunogenicity and protective effects against the killed preparation of S. typhimurium.